SIKAP TURKIYE DALAM KONFLIK AZERBAIJAN-ARMENIA - Yudnovon, Welsa Alfiona Putri; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This article aims to determine and analyze Turkey's interests in supporting Azerbaijan during the armed conflict between Azerbaijan and Armenia in 2020. The main focus of this article is on Turkey's role in supporting Azerbaijan politically, militarily and diplomatically during the war. This article uses a neorealist perspective, with a lavel actor analysis. This article also uses the theory of National Interest. The method used in this paper is qualitative research and is explanatory-analytical in nature by searching several existing literature such as books, journals, internet articles, as well as various sources combined and used to complete the needs of this paper. The result of this article is Turkey's other national interest in its support for Azerbaijan, namely to show Turkey as a regional power actor. Changes in Turkiyesh foreign policy have enabled Turkey to establish strategic relations with its neighboring countries, one of which is Azerbaijan. In the Azerbaijan-Armenia conflict, Turkey provided active support to Azerbaijan by providing military assistance, including increasing the number of military troops and war equipment. In addition to military support, Turkey is also seeking to expand its influence in the region through economic and political initiatives. Economic investments, cooperation in infrastructure projects, and trade agreements are part of Turkey's strategy to create closer ties with Azerbaijan. Through various military supports, active diplomacy and economic initiatives, Turkey seeks to achieve its long-term goals of strengthening its position as a main actor in the dynamics of the Nagorno-Karabakh conflict as well as to secure political and economic interests, especially in efforts to protect Turkey's energy security interests. Keywords: cooperation, dependence, energy security, national interests, strategy